PRODUCTIVITY OF THE Thalassiosira sp. CULTIVATED IN OUTDOOR PHOTOBIOREACTORS - DEWI (NIM : 20511309), ROSMAYA
Previous study showed that the diatom Thalassiosira sp. was potential as a source of biodiesel fuel from lipids (oils). To determine biomass and oil productivity in large-scale outdoor photobioreactors, the present study investigated the optimization of growing medium composition and biomass production. Optimization of growing medium composition was carried out using macronutriens obtained from fertilizers as TSP-36 as a phophorous source and Si- P-(PG) as a silicon source. The optimization of cell growth was performed using indoor photobioreactors with conditions of 13.50 μmol m-2 s-1 light intensity, 24:0 light-dark photoperiod, and 30 ppt salinity. In the feasibility test of fertilizer medium as well as Walne medium, the cells were grown in conditions of 13,50 μmol m-2 s-1 light intensity, 24:0 light-dark photoperiod, and 30 ppt salinity. In addition, the growth conditions of 12:12 light-dark photoperiod, 81 μmol m-2 s-1 light intensity, and 30 ppt salinity were also carried out.